2009
DOI: 10.1016/j.intimp.2009.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Soybean protein fraction digested with neutral protease preparation, “Peptidase R”, produced by Rhizopus oryzae, stimulates innate cellular immune system in mouse

Abstract: A soybean protein fraction was prepared from defatted soybean seed flour and digested with 29 kinds of commercially available protease originating from preparations of animals, plants, and microorganisms. Some digests, in particular, Ro-digest prepared using a Rhizopus oryzae neutral protease preparation (Peptidase R), displayed strong

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
(34 reference statements)
1
19
0
Order By: Relevance
“…As mentioned in the Introduction section, we demonstrated that a glutamine-rich peptide derived of soybean protein fraction stimulates the cellular immune response in the mouse (3,4). Ito et al also reported that isoflavones in a fermented soybean product might modulate the immune systems and prevent liver cancer in the mouse (12).…”
Section: Discussionsupporting
confidence: 65%
“…As mentioned in the Introduction section, we demonstrated that a glutamine-rich peptide derived of soybean protein fraction stimulates the cellular immune response in the mouse (3,4). Ito et al also reported that isoflavones in a fermented soybean product might modulate the immune systems and prevent liver cancer in the mouse (12).…”
Section: Discussionsupporting
confidence: 65%
“…It is known that food components including bacteria penetrate the mucosal barrier via M cells, which endocytoses and transports the components into the Peyer's patches, and initiates immune responses (29). In our previous study (8), we demonstrated that the oral administration of Ro-digest stimulated the innate cellular immune systems in mice. The H1 in the Ro-digest is considered to remain unabsorbed from intestinal tracts because of its higher molecular mass (2549.18).…”
Section: Immunomodulatory Activity Of Chemically Synthesized Glutaminmentioning
confidence: 87%
“…Moreover, DNA microarray analysis showed that the gene expression related to the innate immune response in Peyer's patch cells increased in mice given the diet ( 8 ). In this study, we characterized an immunostimulating peptide in the soybean protein fraction digested with Peptidase R (Ro-digest).…”
Section: Cd11bmentioning
confidence: 99%
See 2 more Smart Citations